Antitumor and human topoisomerase II-α inhibitory activity II-α of the flavonoid luteolin isolated from Prosopis juliflora - Diniz, Rosiane Aleixo (2022)
This study aimed to evaluate the antitumor and inhibitory activity of human topoisomerase II-α of the flavonoid luteolin isolated from Prosopis juliflora against prostate tumor cells (PC-3), with the aim of investigating new drugs of natural origin. In vitro tests were conducted with crude leaf extracts against PC-3 and FGH cell lines. Cytotoxicity tests were performed using MTT (3-(4,5-dimethiazol-2yl) 2,5-diphenyl tetrazolium bromide) with monitoring after 24 h of exposure of tumor and non-tumor cells to different concentrations of extracts (100; 50; 25; 10 μg/mL). Luteolin extracted from the leaves of P. juliflora showed positive results on the DNA topo II-α enzyme essential in the replication process of cancer cells from the 50 µM concentration. Furthermore, it showed antitumor activity against PC-3 cells from the lowest concentration tested 10 µM, and absence of cytotoxicity against normal cells. A chemical study for the extraction and isolation of active compounds from P. juliflora leaf extracts is suggested, to investigate the possible antitumor activity of these compounds in in vitro and in vivo assays.